Identification of LDPE Grades Focusing on Specific CH2 Raman Vibration Modes. (15th April 2013) - Jumeau, Richard; Bourson, Patrice; Ferriol, Michel; Lahure, François; Ponçot, Marc; Dahoun, Abdesselam
Abstract : The possibilities of applications of vibrational spectroscopy techniques (Raman spectroscopy) in the analysis and characterization of polymers are more and more used and accurate. In this paper, our purpose is to characterize Low Density Poly(Ethylene) (LDPE) grades by Raman spectroscopy and in particular with CH2 Raman vibration modes. With temperature measurements, we determine different amorphous and crystalline Raman assignments. From these results and on the basis of the evolution of CH2 bending Raman vibration modes, we develop a phenomenological model in correlation with Differential Scanning Calorimetry and in particular with crystalline lamella thickness determination.